Kontribusi dan elastisitas subsektor dalam sektor pertanian di Kabupaten Tebo - Gumilar Wijaksana; Muhammad Safri; Parmadi Parmadi (Jurnal Paradigma Ekonomika, 2017)
This study aims to analyze: 1) the contribution of the subsector in the agricultural sector to the GRDP in Tebo Regency; 2) the elasticity of the sub-sector in the agricultural sector towards increasing GDP in the Regency. The results showed that the contribution of each agricultural sub-sector to the Tebo Regency GRDP, for the food crop sub-sector an average of 9.45% per year, the plantation subsector was 28.17% per year, then the forestry sub-sector was 7.20% per year, for the sub-sector livestock by 5.83% per year and the fisheries subsector lastly by 0.50% per year. During the period of 2001-2014 the elasticity of each agricultural sub-sector (food crops, plantations, forestry, livestock and fisheries), was under the number 1, so that all of them were inelastic. Even based on statistical tests, the two sectors did not show a significant effect, namely the food crop and livestock subsector. This shows that the increasing role of each agricultural sub-sector is less effective in increasing GRDP in Tebo Regency